A thio-functionalized zinc phosphite with a large-channel framework and enhanced removal ability of mercury ion from aqueous solutions. Issue 32 (14th July 2020) - Hsieh, Jui; Chen, Ju-Ying; Li, Han-Ying; Liu, Hsin-Kuan; Tu, Hsiung-Lin; Wang, Chih-Min
Abstract : New thio-functionalized zinc phosphite (NTOU-2S ) exhibited the different structural properties and removal ability of Hg 2+ cation from the sulfur-free NTOU-2 . Abstract : The first example of a thio-functionalized zincophosphite material (NTOU-2S ) incorporating the 2, 5-thiophenedicarboxylate (TPDC) ligands was synthesized using a hydro(solvo)thermal method and structurally characterized by single-crystal X-ray diffraction. Interestingly, the perspective view of the crystal structure for NTOU-2S is similar to our previous report of NTOU-2 but the carboxylate organic ligands (TPDC for NTOU-2S ; 1, 4-benzenedicarboxylate, BDC, for NTOU-2 ) in both compounds adopt different types of bis-monodentate coordination models (the unusual cis bonding versus a trans linkage) to bridge the metal atoms of inorganic tubes in the formation of large-channel zincophosphite frameworks, resulting in structural and functional diversities. The thiophene-based compound also displayed higher thermal stability and removal ability for the softer Hg 2+ cations from water solutions than the performance of sulfur-free NTOU-2 . In addition, the synthesis, structural characteristics, removal properties of heavy metal cations, and thermal and chemical stabilities for both compounds were also reported.